A Statistical Analysis of Cost and Yield Optimisation: A Comparison between Indigenous Technical Knowledge Systems and Scientifically Tested Systems used by Crop farmers in Gweru East, Zimbabwe - A, Shiri; S, Chirume; H. H, Mabika (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2016)
This study sought to compare the effectiveness of indigenous technical knowledge systems (ITKS) and scientifically tested systems (STS) used to minimise costs and maximise crop production by various farmers in Gweru East of Zimbabwe. The study specifically analysed the farming methods used by the crop farmers and compared the methods in terms of finance costs, output, efficiency and effectiveness. Since farmers belong to different categories such as small scale, medium and commercial/large scale, the stratified random sampling technique was used to select the farmers. The sample size was fifty farmers out of a population of 582. The farmers were asked to complete a structured questionnaire which had been subjected to a peer-check for validity and reliability. Two of the famers in each category were purposively sampled and informally interviewed to shed more light on their indigenous knowledge about the farming methods. Independent samples t-tests were used to test for the significance of the differences in the means of the costs and crop out-put between the different groups of farmers who used the two different farming methods. The results of this study showed that for cost of fertilizer, there were significant mean differences between ITKS and STS (t=7.2143) [STS being higher] and between ITKS and BOTH (t=2.2127) [BOTH being higher and being a combination of STS and ITKS]. However there were no statistically significant differences between STS and BOTH. Although mean differences between ITKS and STS, between ITKS and BOTH and between STS and BOTH were observed for cost of controlling pests, they were not statistically significant. For cost of controlling diseases, there were significant mean differences between ITKS and STS (t=7.218) [STS being higher], and no statistically significant differences between ITKS and BOTH and between STS and BOTH. For crop out-put per hectare, there were significant mean differences between BOTH and STS (t=2.140) [STS being higher]. There were no significant mean differences in the crop out-put per hectare between ITKS and STS and between ITKS and BOTH. In the interview excerpts and open-ended sections of the questionnaire, farmers gave a description of some of the ITKS that they used and outlined their effectiveness in terms of crop yield and cost minimisation. The results are critical as they advice farmers on the best practices that they can use to maximize production and reduce poverty in the communities. African universities are advised to focus their research on institutionalizing indigenous technical knowledge since these are opportunities which have not been taped for a long time. This may enhance the development of banks of African knowledge for African farmers